METHODOLOGICAL BASIS FOR THE DEVELOPMENT OF SPECIAL ENDURANCE IN MIDDLE DISTANCE RUNNERS (Academicia Globe: Inderscience Research, 2022)
The article discusses the methods of development of special endurance in middle-distance runners. The basics of the development of special endurance in athletes-runners in the classroom in groups to improve sportsmanship are given.